Assessing Differentiation in Population Incomes in the Russian Federation with Regard to Inter-Regional Level of Prices - G. Y. Gagarina; R. O. Bolotov (Вестник Российского экономического университета имени Г. В. Плеханова)
The high level of inter-regional social and economic inequality of population incomes forms one of major problems of the space development of the Russian Federation. This situation promotes social tension and hinders economic growth in the country. The article analyzes the current standing of the inter-regional inequality in the Russian Federation by a number of key indicators characterizing population incomes and estimates dynamics of inequality changes in entities of the Russian Federation within the period of 2000–2020. Findings of the analysis prove that inter-regional differentiation of entities of the Russian Federation by the level of population incomes from 2000 to 2020 dropped in more than 1.5 times. The current level of differentiation is not considerable and the sample of Russian Federation entities by this criterion can be called homogeneous. All calculations were made with necessary adjustment of the nominal level of incomes to the regional level of prices.